2021
DOI: 10.1111/anu.13299
|View full text |Cite
|
Sign up to set email alerts
|

The influence of dietary β‐1,3‐glucan on growth performance, feed utilization, antioxidative and immune status of Pacific white shrimp, Litopenaeus vannamei

Abstract: Pacific white shrimp (Litopenaeus vannamei) is a species of the Penaeidae family indigenous to the east coast of the Pacific Ocean and has been cultured worldwide in intensive and semi-intensive systems (Li et al., 2015). The burgeoning shrimp aquaculture industry has been plighted by problems of pathogens and deleterious environmental conditions, which lead to oxidative stress, shrimp epidemics and depression of physiological and immunological responses in shrimp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 73 publications
1
4
1
Order By: Relevance
“…Indeed, the present results suggested that the expression of intestinal LGBP was significantly increased in shrimp fed β-1,3-glucan diet, together with an enhancement in immunity parameters in intestinal tissue and serum. Additionally, β-1,3-glucan supplementation enhanced the antioxidant capacity of shrimp, and similar results were also observed in white shrimp fed β-1,3-glucan ( 7 ). HSP70 serves as an important oxidative stress biomarker ( 49 ), and higher expression of HSP70 in the intestinal tissue shrimp fed β-1,3-glucan confirmed the antioxidant property of β-glucan again.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Indeed, the present results suggested that the expression of intestinal LGBP was significantly increased in shrimp fed β-1,3-glucan diet, together with an enhancement in immunity parameters in intestinal tissue and serum. Additionally, β-1,3-glucan supplementation enhanced the antioxidant capacity of shrimp, and similar results were also observed in white shrimp fed β-1,3-glucan ( 7 ). HSP70 serves as an important oxidative stress biomarker ( 49 ), and higher expression of HSP70 in the intestinal tissue shrimp fed β-1,3-glucan confirmed the antioxidant property of β-glucan again.…”
Section: Discussionsupporting
confidence: 71%
“…The bglucan has been widely applied to the aquaculture industry due to its positive impact on the health of aquatic animals (5,6). Numerous studies in b-1,3-glucan have confirmed its property of antiinflammatory, immune-enhancing, and anti-oxidation in aquatic animals such as white shrimp (7)(8)(9), marine swimming crab (Portunus trituberculatus), hybrid striped bass (Morone chrysops × M. saxatilis) (10), and large yellow croaker (Pseudosciaena crocea) (11). Evidence from human hepatocytes suggested that b-1,3-glucan could attenuate inflammation and accumulation of reactive oxygen species (ROS) induced by lipopolysaccharide (12).…”
Section: Introductionmentioning
confidence: 99%
“…However, this was except for ash content in the β-glucan treatment group, with lower levels being measured. In comparison to past studies, white leg shrimp (Litopenaeus vannamei), after being fed with β-glucan had no changes in moisture, crude protein, and lipid contents, but body ash levels had increased (Xu et al, 2021). The addition of dietary zinc in various forms, such as inorganic zinc oxide, organic zinc methionine, or zinc nanoparticles zinc-acetate, did not impact body composition in any of the previous studies on Nile tilapia (Oreochromis niloticus, Baker et al, 2016), coho salmon (Oncorhynchus kisutch, Yu et al, 2021), rabbitfish (Siganus rivulatus, Sallam et al, 2020), or striped catfish (P. hypophthalmus, Kumar, Krishnani, et al, 2017;Singh et al, 2017).…”
Section: Body Compositioncontrasting
confidence: 80%
“…In addition to the growth performance indicators, other indicators, such as digestive enzyme activity, total antioxidant capacity, malondialdehyde content, AKP, ACP activity and so on, all showed the same phenomenon. A previous study found that the addition of 0.064% β-glucan improved the weight gain of L. vannamei [ 42 ]. Moreover, 0.02% dietary β-glucan showed higher levels of immune gene expression in L. vannamei [ 13 ].…”
Section: Discussionmentioning
confidence: 99%